2017
DOI: 10.1111/1462-2920.14000
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation capability and amylosome conservation among diverse human colonic and rumen isolates of the keystone starch‐degrader Ruminococcus bromii

Abstract: Summary Ruminococcus bromii is a dominant member of the human colonic microbiota that plays a ‘keystone’ role in degrading dietary resistant starch. Recent evidence from one strain has uncovered a unique cell surface ‘amylosome’ complex that organizes starch‐degrading enzymes. New genome analysis presented here reveals further features of this complex and shows remarkable conservation of amylosome components between human colonic strains from three different continents and a R. bromii strain from the rumen of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 55 publications
5
95
0
3
Order By: Relevance
“…We previously showed that the ability of R. gnavus to grow on mucin was dependent on the expression of a GH33 intramolecular trans -sialidase ( Crost et al, 2013 , 2016 ; Tailford et al, 2015b ) and that fucose was released from mucin by the action of GH29 and GH95 fucosidases ( Crost et al, 2013 ). In contrast, the R. bromii L2-63 genome encodes a small number of GHs ( Mukhopadhya et al, 2018 ) compared to R. gnavus ATCC 29149 ( Crost et al, 2013 ) (21 in R. bromii L2-63 vs. 60 in R. gnavus ATCC 29149) and no genes encoding mucin-degrading enzymes were found, in line with the inability of this strain to grow on mucin. In addition, its lack of growth in co-culture with R. gnavus , suggests that R. bromii cannot utilize the monosaccharides released by R. gnavus , in agreement with genomic data suggesting that R. bromii does not harbor genes involved in fucose or sialic acid metabolism (Supplementary Figures S1 , S2 ).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…We previously showed that the ability of R. gnavus to grow on mucin was dependent on the expression of a GH33 intramolecular trans -sialidase ( Crost et al, 2013 , 2016 ; Tailford et al, 2015b ) and that fucose was released from mucin by the action of GH29 and GH95 fucosidases ( Crost et al, 2013 ). In contrast, the R. bromii L2-63 genome encodes a small number of GHs ( Mukhopadhya et al, 2018 ) compared to R. gnavus ATCC 29149 ( Crost et al, 2013 ) (21 in R. bromii L2-63 vs. 60 in R. gnavus ATCC 29149) and no genes encoding mucin-degrading enzymes were found, in line with the inability of this strain to grow on mucin. In addition, its lack of growth in co-culture with R. gnavus , suggests that R. bromii cannot utilize the monosaccharides released by R. gnavus , in agreement with genomic data suggesting that R. bromii does not harbor genes involved in fucose or sialic acid metabolism (Supplementary Figures S1 , S2 ).…”
Section: Resultsmentioning
confidence: 87%
“…Ruminococcus bromii L2-63 is highly specialized in starch degradation, dedicating 15 of its 21 GH-encoding genes to putative GH13 amylases ( Ze et al, 2015 ). Some of these GH13 amylases revealed an organization in “amylosome”, contributing to R. bromii exceptional ability to degrade dietary RS ( Ze et al, 2015 ; Mukhopadhya et al, 2018 ). Here we showed that R. bromii was able to utilize both starch substrates (SS and RS) as sole carbon source, in agreement with previous reports ( Ze et al, 2012 , 2015 ) whereas no growth was detected with R. gnavus on these substrates despite the presence of 9 GH13-encoding genes in R. gnavus ATCC 29149 genome.…”
Section: Resultsmentioning
confidence: 99%
“…have lost some of the conserved sporulation genes ( Figure 3B) and have between 48 and 60% of the sporulation signature (Abecasis et al 2013) (Figure S1, Figure S3), in what appears to be an intermediary stage into becoming asporogenous. Still, they were recently shown to sporulate (Browne et al 2016;Mukhopadhya et al 2018), and are likely to spread as spore-like structures between hosts (Schloss et al 2014;Mukhopadhya et al 2018), which plays as a counter evolutionary force to the emergence of asporogenous phenotypes. In other cases, notably Epulopiscium and Candidatus Arthromitus, sporulation has evolved as a reproductive mechanism, involving some gene loss ( Figure 3B) and eventually the gain of new genes (Flint et al 2005;Galperin 2013), under distinct evolutionary forces.…”
Section: Discussionmentioning
confidence: 99%
“…In population-based cohorts, significant associations have been found between dietary factors and interindividual distances in microbiota composition 6, 7, 8, 9, 10 . Culture-based studies have shown that strains from a given species may share substrate metabolism but may also display differences 11, 12 . Consistent with this finding, recent metagenomics-based studies using strain-level profiling tools have revealed functional variation within species associated with dietary habits 13, 14, 15 .…”
Section: Introductionmentioning
confidence: 99%